Reducerade fungiciddoser vid bekämpning av potatismögel - vilka blir följderna? - Jönsson, Magnus; Olsson, Gabriella (SLU/Dept. of Forest Mycology and Plant Pathology, 2015)
Potato late blight, caused by the oomycete Phytophthora infestans, is the most devastating crop disease in potato crop globally and annually cost growers 5 billion USD in losses and control measures. Large quantities of fungicides are used for the control of potato late blight in order to avoid yield loss and to limit the risk of tuber blight. New fungicides have a better ability to achieve a good level of control at lower doses compared to older fungi- cides. A field trial was conducted to investigate if it is possible to lower the dose while maintaining both yield level and a good protection against tuber blight. In the trial, the control of potato late blight using full recommended dose of fungicide was compared to half recommended dose. Generally crop protection salesmen and farmers advice against using half the recommended fungicide dose for the control of potato late blight. It is al- leged that this practice results in a selection of phenotypes of P. infestans which are more aggressive and have a higher fungicide tolerance. To examine if these claims are valid, isolates of P. infestans were collected from plots treated with full dose of fungicide (K2), half dos fungicide (K1) and untreated plots (K0). The collected isolates were tested for aggressiveness by measuring latency period, lesion growth and spore production. In addi- tion, test for mycelial growth on agar amended with three levels fungicide were performed. Tests were carried out with all three fungicide used in the field trial; Infinito, Ranman Top and Revus Top. Microsatellites were used as markers to detect genotypic differentiation between the three sets of samples. Results from the aggressiveness tests showed that no significant differences in aggres- siveness could be found between the isolates from K2 and the isolates from K1. Only iso- lates from K0 were significantly less aggressive. The mycelial growth on fungicide amended agar was significantly higher for isolates from K2 in all tests except one dose level, in one fungicide. The differences in mycelia growth among isolates from K0 and K1 varied. The infection of P. infestans in the field trial was low and no differences in yield or occurrence of tuber blight were found. No genotypic differentiation was detected despite the significant differences in aggressiveness between samples collected from the different treatments. This indicates that the observed differences in phenotype are due to changes in the gene expression rather than in the population structure. Collectively the results show that usage of half the recommended dose of fungicide did not increase aggressiveness, reduce yield, increase fungicide tolerance or occurrence of tuber blight in the field trial. Full dose however increased phenotypic fungicide tolerance.